(untitled) (Journal of Applied Learning and Teaching, 2021)
The views on plagiarism of teaching staff working at four Australian universities operating in Singapore were investigated through a survey and interviews. This was carried out through analysis of their responses to six different plagiarism scenarios, of their replies to open-ended questions and of interview comments. Although staff were found to have a good understanding of the different cases of plagiarism, nearly half of them indicated that they would accept up to 15% of plagiarized material, with 30% of them willing to accept 20% or more. This indicates the need for an improved staff education on plagiarism. Furthermore, the majority of the teaching staff expected their students to plagiarize, implying the need for a more effective teacher - student interaction. A set of interactive measures between faculty, teaching staff and students is recommended to ensure and sustain an environment of academic integrity within the transnational higher education sector.